(untitled) (Balneo and PRM Research Journal, 2024)
Background: The aim of the study was to investigate the effecs of mofettes and carbonated mineral water baths on bone healing using a rat femoral defect model; (2) Methods: A 2mm diameter unicortical defect in the left femoral diaphysis in 40 Wistar Rats was surgically created. Furthermore, the subjects were divided into 4 treatment-groups: control, mofette therapy, mofette therapy and carbonated mineral water bath, and carbonated mineral water bath. At the end of the 2-week treatment and at 4 and 6 weeks, the animals were evaluated through Micro-CT analysis of the bone defect and histological analysis of bone tissue and skin; (3) Results: The processes of bone consolidation and repair are not completed at 6 weeks in all groups. However, comparing the proliferated bone tissue in the created orifice and the degree of thickening of the femoral wall, it can be affirmed that at 6 weeks, the best results are present in Group 4, treated with carbonated mineral water baths, followed by the combination of mofettes and carbonated water. (4) The use of these treatments could open a new possibility for shortening the healing time in patients with bone defects, as it is non-invasive and accessible. Keywords: mofette; carbonated mineral water; bone defect; bone healing